2010
DOI: 10.1002/jssc.201000005
|View full text |Cite
|
Sign up to set email alerts
|

Micellar and aqueous‐organic liquid chromatography using sub‐2 μm packings for fast separation of natural phenolic compounds

Abstract: The objective of the present work was to investigate the chromatographic behavior of natural phenolic compounds in micellar and aqueous-organic LC using a short column packed with 1.8 microm particles. Firstly, the effect of ACN and SDS on elution strength and selectivity was examined by isocratic submicellar (0-30% ACN/5% 1-butanol/1-6 mM SDS) and micellar (0-30% ACN/5% 1-butanol/40-60 mM SDS) systems. The varied concentrations of two modifiers in the mobile phases revealed different eluting power. Then, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Nevertheless, the micellar systems can also be applied for this purpose. The comparison of the separation of several natural phenolic compounds with micellar, submicellar, and water-organic HPLC systems equipped with C-18 column has been presented by Cao and co-authors [21]. The process of the optimisation of solute separation in silico based on the experiments performed with MLC-HPLC modes has been proposed by Hadjmohammadi and co-authors in series of papers [2224].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the micellar systems can also be applied for this purpose. The comparison of the separation of several natural phenolic compounds with micellar, submicellar, and water-organic HPLC systems equipped with C-18 column has been presented by Cao and co-authors [21]. The process of the optimisation of solute separation in silico based on the experiments performed with MLC-HPLC modes has been proposed by Hadjmohammadi and co-authors in series of papers [2224].…”
Section: Introductionmentioning
confidence: 99%
“…(1) sulphaguanidine, (2) sulphanilamide, (3) sulphacetamide, (4) sulphadiazine, (5) sulphathiazole, (6) sulphapyridine, (7) sulphamerazine, (8) sulphamethazine, (9) sulphamethizole, (10) sulphamonomethoxine, (11) sulphachloropyridazine, (12) sulphamethoxazole, (13) sulphisoxazole, ( 14) sulphadimethoxine, and ( 15) sulphaquinoxaline, all from Sigma (St. Louis, MO, USA). Also, four alkylbenzenes (ethylbenzene, propylbenzene, butylbenzene and amylbenzene) from Sigma were used to evaluate the relative polarity of the stationary phase under hydro-organic and micellar conditions.…”
Section: Reagents and Columnsmentioning
confidence: 99%
“…Only a few studies concerning gradient elution have been reported on MLC. [6][7][8][9][10][11][12][13][14] Most reports apply gradients of organic solvent (acetonitrile, butanol or pentanol), and keep the concentration of the surfactant (always the anionic sodium dodecyl sulphate, SDS) constant. Only Bryant and Altria used simultaneous gradients of SDS and organic solvent (pentanol).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the various reports on the feasibility of MLC in the pharmaceutical analysis of drugs and other biologically active compounds , there are only a few reports about the analysis of natural polyphenolic compounds using MLC , but none of them have reported the simultaneous separation of phenolic acids and flavonoids. In this study, the simultaneous isocratic separation of five phenolic acids (galic, chlorogenic, caffeic, p ‐coumaric, and ferulic acid) and four flavonoids (myricetin, morin, quercetin, and kaempferol) were investigated in three different RPLC modes using hydro‐organic mobile phase, micellar mobile phase as well as mobile phases containing SDS in concentrations lower than the CMC (submicellar LC ).…”
Section: Introductionmentioning
confidence: 99%